Associação da contagem de celulas somaticas no leite e a rentabilidade de fazendas leiteiras - Vicente, Fábio Henrique (2023)
The aim of this research was to analyze the association between somatic cell count in milk and the profitability of dairy farms. Specifically, the objectives were to quantify the influence and representativeness of cost components on operational and total costs, as well as on the revenue of the dairy activity, and to compare the socio-economic differences among rural properties in the formed clusters. Data from 290 properties located in the state of Minas Gerais, which participated in the technical assistance project Educampo, by Sebrae Minas, in the year 2018, were analyzed. The dairy farms were grouped into three clusters, according to the somatic cell count (SCC): from 50,000 cells/mL to 366,000 cells/mL (Cluster 1); from 366,000 cells/mL to 600,000 cells/mL (Cluster 2); and > 600,000 cells/mL (Cluster 3). The cost of milk production was estimated according to the methodologies of total cost and total operational cost. Descriptive analysis, variance test (ANOVA) with mean difference test by Tukey method, at the significance level of 5%, was performed using IBM SPSS® software. Among the main factors associated with SCC, producer's education level, the producer having the property as the main source of income, milking frequency, and water quality stood out. The bonus for the milk price according to SCC had greater representativeness in the difference between the clusters, in relation to the total bonus value, playing a significant role in the total revenue. Cluster 1 farms, with lower SCC, had higher costs for feeding, compost barn and free stall bedding management, and artificial insemination than the other clusters. The results obtained indicate an inverse association between SCC and revenue in dairy farming, thus contributing to increased profitability on dairy farms. The reduction in SCC contributed to an increase in gross revenue, gross and net margins, and the profit of dairy farms.